Wastewater characterization towards cleaner production in leather tanning industry in Palestine - Al-Houriny, Heba; sbaih, Mariam; Nammoura, Israa (جامعة بوليتكنك فلسطين - بنية تحتية, 2020)
The present study aims to characterize the wastewater from leather tanning industry in Palestine in order to determine the pollution load .Wastewater samples was collected from all leather manufacturing processes released from cow hides. From various tanneries in Hebron district. The experimental work for the characterization of wastewater presented by analyze , chemical oxygen demand (COD) , electrical conductivity (EC) , total solids (TS) , total dissolved solids (TDS) , total suspended solids (TSS), PH , ammonia (NH3) and chromium in both states Cr(III) ,Cr(VI) . The analysis results for the physiochemical characteristics shows the following. The PH of the wastewater shows a high variation depending on manufacture process, the wastewater generated from liming&deliming process comes with alkaline properties have a PH value of ( 8-12 ) , whereas wastewater comes from pickling & tanning process have an acidic properties with PH values ranged ( 2-4 ).The highest COD value of the wastewater among the leather manufacturing process was detected in liming&Unhairing process with an average value of ( 8000 ) .studying the TS,TSS and TDS values it was found the washing process generate the wastewater that have the high value. The wastewater generate from tanning process is the only effluents that contains chromium with the amount of ( 3500 ), as a form of Cr+3, also a little amount hazardous Cr+6 might be found. According to the mentioned results we can say that the pollution loads in the wastewater is really high. Through tracking the producing one ton of hide, the amount of wastewater generated was approximately 10m3 .
CD , no of pages 63 , بنية تحتية 5/2020
Keywords: Wastewater characterization; leather tanning industry